Image Caption Detector Using LSTM and CNN - Meghana, Atyam Mehermani; B. Sekharbabu, B. Sekharbabu (Journal of Neonatal Surgery, 2025)
In computer vision, the general quality is determined by how well the image is comprehensible. Image Captioning is a concept where many models are proposed for a better understanding of the image. In recent times, this technology has been used in many fields like recommendation systems, News channels, Accident detection, and many more. The existing deep learning technique is the Bag of Words model, Spatial pyramid matching and Markov models are used for the automation caption generation but have difficulty in capturing content. So, the proposed methodology is LSTM and CNN are used for effective image representation and have end-to-end learning of the image. VGG16 is used for feature extraction as it has the benefit of hierarchical feature representation. This paper uses the Flickr8K dataset and contains the images along with the five different captions concerning each image. After training, the predictions are made on the model and then evaluated using the metrics BLEU 1, and BLEU 2 which measure the overlapping of the words between generated captions and reference captions and achieves better results than existing models